Analysis of Clean and Healthy Living Behaviour Indicators in Caturtunggal Village and Implications for Public Health Behaviour - Sejati, Ardhitya; Kurniawati, Erna Yovi (Agribiohealth (Journal of Agriculture, Biology & Health Sciences), 2025)
Clean and Healthy Living Behaviour (PHBS) is a key strategy in improving public health. However, its implementation in areas with diverse socio-cultural characteristics, such as Caturtunggal Village, requires thorough monitoring. This study used a quantitative approach with a cross-sectional descriptive design. A total of 528 households in Caturtunggal Village were respondents through an online questionnaire based on 13 indicators of PHBS according to the Indonesian Ministry of Health guidelines. The results showed that most households had high achievements in PHBS (150 households = 100%, 155 households = 90%). However, there were disparities in achievement (56 HH = 70%, 3 HH = 40%), especially in indicators of promotive behaviours such as exclusive breastfeeding, physical activity, and not smoking at home. This disparity is due to economic differences, health literacy, and social support. Community-based interventions, increasing the role of cadres, and cross-sector collaboration need to be strengthened. The success of high PHBS achievements must be balanced with adaptive and participatory strategies to overcome inequalities between community groups. Regular evaluation and locally based policies are key to the sustainability of the PHBS program.